Augmented Zika and Dengue Neutralizing Antibodies Are Associated With Guillain-Barré Syndrome. (3rd August 2018) - Lynch, Rebecca M; Mantus, Grace; Encinales, Liliana; Pacheco, Nelly; Li, Guangzhao; Porras, Alexandra; Mendoza, Alejandro R; Peng, Jin; Rengifo-Pardo, Monica; Cruz, Magelda Montoya; Harris, Eva; Bethony, Jeff M; et al.
Abstract: The role of neutralizing antibodies in Zika-induced Guillain-Barré syndrome (GBS) has not yet been investigated. We conducted a case-control study using sera from the 2016 Zika epidemic in Colombia to determine the neutralizing antibody activity against Zika virus (ZIKV) and dengue virus serotype 2 (DENV2). We observed increased neutralizing antibody titers against DENV2 in ZIKV-infected individuals compared with uninfected controls and higher titers to both ZIKV and DENV2 in ZIKV-infected patients diagnosed with GBS compared with non-GBS ZIKV-infected controls. These data suggest that high neutralizing antibody titers to DENV and to ZIKV are associated with GBS during ZIKV infection. Abstract : We conducted a case-control study using sera from the 2016 Zika epidemic in Colombia and found that high neutralizing antibody titers to dengue virus and Zika virus (ZIKV) were associated with Guillain-Barré syndrome during ZIKV infection.